CORPORATE FINANCIAL DISCLOSURE IN NIGERIAN DEPOSIT MONEY BANKS - Ayodele, Thomas Duro; Afolabi, Taofeek Sola (Advances in Social Sciences Research Journal, 2018)
The study examined the impact of corporate financial disclosure on the performance of Nigerian Deposit Money banks. It evaluated the extent to which Nigerian Deposit Money banks complied with the financial disclosure requirements as given by the monetary authorities. Primary data collected through questionnaire were used for the study. Out of 120 copies of questionnaire served on respondents, 100 copies were recovered and used for the analysis of the study. The analytical tools used for the study are the t-test and the Analysis of variance (ANOVA). From the hypotheses tested, the results show that corporate financial disclosure has a significant influence on the banks’ stability and performance in the Nigerian financial sector. Therefore, the study concludes that the corporate disclosure of financial reporting practices by banks in general will enable them to work towards improving and managing their non-performing loans effectively and efficiently for stability and hence better performance. It was therefore recommended among others that efforts should be geared towards improved corporate financial disclosure among money Deposit Money banks in Nigeria and mandatory compliance with the code of corporate governance and effective legal framework which specifies the rights and obligations of banks, it’s directors and shareholders.